Multicultural environment in higher education: The knowledge and perceptions of medical teachers of UNIKL RCMP, Malaysia - Emdadul Haque, ATM; Haque, Mainul; Wan Dali, Wan Putri Elena (Australasian Medical Journal, 2017)
Background A clear majority of teaching staff in UniKL-RCMP are expatriates with different cultural backgrounds, and the university currently accepting international students with a different cultural background in addition to the local culturally diverse students. Aims The purpose was to determine the knowledge and awareness of the lecturers of Faculty of Medicine regarding multiculturalism and the importance in the medical profession. Methods This was a cross-sectional study. A questionnaire was developed based on the relevant demographic information and knowledge and awareness of the cultural issues and the validity was discussed with a survey expert. Results A total of 43 teachers took part in the survey. The respondents were mostly male, expatriate and had very fewer experiences in teaching students of different cultural background. The most important thing affecting teachers’ competence was their experience in teaching students of different culture, and the teachers with experience in teaching in a multicultural environment felt more competent than the ones without experience. Gender or teaching experience did not have a significant impact on their feeling of competence. However, the teachers believed that training on special education program might have helped them more than their educational background to help develop the cultural competence of the students from different cultural backgrounds. Conclusion This study showed that teachers need more training and experiences of the multicultural education program and to facilitate the development of cultural competence of students with cultural diversity, which should be taken into consideration in the faculty development activities